STRATEGI PENINGKATAN NILAI-NILAI KECERDASAN EMOSIONAL DALAM PENGELOLAAN (MANAJEMEN) SUMBER DAYA MANUSIA DI PERGURUAN TINGGI KEAGAMAAN ISLAM - Thoha, Mohammad (STAIN PAMEKASAN, 2018)
Emotional Quotion contributes 60% to someone’s success. The main characteristic of the individual emotional quotion is when he is successful to implement his emotional potency in daily life. Emotional potency here actually has been given to people before the birth. But, this potency can be increasing or decreasing as it is taken care of or developed. Based on the literature review of psychology literation and comparing to juridical analysis about regulation in managing the State Islamic University, this research comes into a finding of how to develop the emotional quotion for the State Islamic University managers. Every individual, including the lecturer and the leader of the State Islamic University can increase their emotional quotion’s value, when they can: first, recognize their own emotional states as well as others; second, manage their own emotion as well as others, and three, motivate themselves as well as others